Pengaruh Pendidikan Kesehatan tentang Pencegahan Perdarahan Post Partum terhadap Tingkat Pengetahuan Ibu Hamil Trimester III - Faizaturrahmi, Eka; Siswari, Baiq Disnalia (STIKes Hamzar, 2025)
Prevention of postpartum hemorrhage can be prevented as early as possible, starting from when the mother is pregnant by carrying out good antenatal care. Mothers who have a predisposition or history of postpartum hemorrhage are advised to give birth in a hospital. One way that can be done to prevent postpartum hemorrhage is by increasing the knowledge of pregnant women by providing health education so that awareness will arise in individuals or communities to behave according to the knowledge they have. The purpose of the study was to determine the effect of health education on preventing postpartum hemorrhage on the level of knowledge of pregnant women in the third trimester in the Teratak Health Center Work Area. Method: pre-experimental design with One group pre and posttest design. The sample of this study was some of the third trimester pregnant women in the Teratak Health Center Work Area in December 2023 as many as 44 people, with the inclusion criteria: Third trimester pregnant women who live in the Teratak Health Center Work Area, are willing to be respondents, who can communicate well, who can read and write. Data analysis using the Wilcoxon test. Results: Knowledge before the intervention was mostly good as many as 23 respondents (52.3%). Knowledge after the intervention was mostly good as many as 29 respondents (65.9%). Conclusion: There is an Influence of Health Education on Postpartum Hemorrhage Prevention on the Level of Knowledge of Pregnant Women in the Third Trimester in the Teratak Health Center Work Area with a p-value of 0.002 <0.05.